(untitled) (Biodiversitas Journal of Biological Diversity, 2016)
Hajizadeh G, Kavosi MR, Jalilvand H. 2013. Evolution of oviposition behavior in gypsy mothÂ (Lymantria dispar) in Hyrcanian forests, North of Iran. Biodiversitas 14: 101-105. Oviposition behavior has been introduced at the center of many of the major debates on theÂ ecology and evolution of interactions between insects and plants. The objective of this research was to determine the number of eggÂ masses gypsy moth in relation to diameter at breast height (dbh), egg placement, orientation and host tree species. Sampling was carriedÂ out in Daland national park, Gorgan province. By global position system (GPS) device using polygons with width of 20 m andÂ determined azimuth, defoliated trees were recorded. Data and means were compared using Duncan’s multiple range tests. ResultsÂ showed that the diameter at breast height was not significantly affected by the number of egg masses. The effect of oviposition place onÂ number of egg masses gypsy moth were significant (P<0.01).Â The highest number of egg masses (2.148 egg masses/tree) was observedÂ at trunk of defoliated trees; also, minimum (1.65 egg masses/tree) occurred in branches of defoliated trees. The effects of ovipositionÂ orient were significant (P<0.05). The means comparison showed that the maximum rates of egg masses was occurred in the southÂ geographical position (2.04 egg masses/tree),Â the least of defoliation was related to the north direction (1.57 egg masses/tree). TheÂ primary host tree species was Persian iron wood (Parrotia persica). In finally, the selectivity of oviposition females may often provideÂ the initial basis for divergence of insect populations on to different plant species, and it may drive the evolution of some plant defenses.